Dampak Pariwisata terhadap Kemiskinan di Kawasan Pariwisata di Bali - I Nyoman Sudiarta; I Wayan Suardana (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
This study aims to determine the typology of poverty, it causes and its impact on the poor in the tourism area of Tulamben Tourism and Candidasa in Karangasem regency. Research using purposive sampling method with a sample size 94 coastal residents. Data analyzed by using descriptive statistics. The research results are as follows: (i) Typology of poverty of coastal communities, among others: the age of majority is 60 years old and above, low education (graduated primary school), the average income of 300,000/ month, (ii) Causes of poverty included natural factors, cultural factors, and the lack of poor people to work in the tourism sector, and (iii) the impact of tourism on coastal communities positively impact the chances of opening new jobs like being a tour guide of diving, porter, and souvenir sellers.